A First Step in Understanding Influences on System-Involved Women's Changes in Financial Need. (July 2023) - Sanders, Kaelyn; Hoskins, Kayla; Morash, Merry
Financial need strongly predicts women's recidivism. However, little is known about influences on change in system-involved women's financial need. Qualitative data from women with significant increases and decreases in financial need show the importance of tailored assistance finding jobs to improve financial status, and the relevance of worsening physical health and limited access to safety-net benefits to increasing financial need. Prior convictions act as a barrier to employment especially for Black women, and younger women most often associated financial problems with lack of mental health care. Gender, race, and age responsive assistance is needed to improve system-involved women's financial standing.